Prevention of venous thromboembolic complications in oncological surgery (review of the literature) - A. M. Karsanov; A. A. Kulchiev; A. K. Khestanov; A. A. Morozov; S. V. Tigiev (Вестник хирургии имени И.И. Грекова)
The multifactorial nature of the problem of venous thromboembolic complications (VTEC) in oncological surgery underlies that, despite the widespread introduction of risk criteria and routine thromboprophylaxis in practice, it is not possible to completely prevent these postoperative complications. Ensuring the highest level of patient safety for VTEC is one of the priority tasks of the surgical service specialists. Surgical practice requires the development of reasonable criteria for prolonged medical prophylaxis of VTEC and the introduction of methods for the early detection of latent venous thrombosis.